2016
DOI: 10.1007/s13744-016-0415-9
|View full text |Cite
|
Sign up to set email alerts
|

Biological Strategies of Dermestes maculatus DeGeer (Coleoptera: Dermestidae) at Larval Stages in Different Temperatures

Abstract: The intraspecific variation in larval instars is a widely distributed phenomenon amongst holometabolous insects. Several factors can affect the number of instars, such as temperature, humidity, and density. Only a few references could be found in the literature because the invariability in the number of larval instars is considered normal, and the issue has raised little to no interest. Despite this, no study to date has intended to assess or focus on the larval development. Here, we analyzed the effect of dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
0
5
0
1
Order By: Relevance
“…This was not a surprise because those results were already observed when D . maculatus development was studied under controlled conditions [28, 32, 53, 54]. Thus, we did not attribute that to fluoxetine.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This was not a surprise because those results were already observed when D . maculatus development was studied under controlled conditions [28, 32, 53, 54]. Thus, we did not attribute that to fluoxetine.…”
Section: Discussionmentioning
confidence: 99%
“…Extra larval instars and prolonged development times can be observed when conditions are adverse [30, 31]. Several factors can affect the number of instars in insects: temperature, photoperiod, food quality and quantity, humidity, density, presence of lesions, genetics, among others; and these variables can interact among them [32]. Each insect species has a characteristic threshold size, and a larva must reach it before metamorphosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dermestid larvae thrive in warm and dry environments, actively avoiding both excessive light and humidity (Charabidze et al 2014). Studies have shown that dermestid larvae survival is highest when temperatures are between 20-30°C and their period of activity is restricted to the warmest months of the year (Amos 1968, Raspi and Antonelli 1996, Zanetti et al 2016a, 2016b, Martín-Vega and Baz 2012, Martín-Vega et al 2017. Thus, their presence can indicate seasonality.…”
Section: Dermestid Beetlesmentioning
confidence: 99%
“…Esta especie se desarrolla preferentemente en la superficie, pero sus larvas poseen fototropismo negativo (Martin y West, 1995). El desarrollo de D. maculatus abarca de 23 a 107 días y requiere temperaturas entre 15 ºC y 35 ºC (Martin y West, 1995;Richardson y Goff, 2001;Zanetti et al, 2015c); el aumento de la temperatura constituye un factor de aceleración del proceso (Zanetti et al, 2016). La presencia de Dermestidae se ha registrado desde las etapas tempranas de descomposición cadavérica, pero su abundancia ocurre en las etapas avanzadas (Oliva, 2001;Centeno et al, 2002;Zanetti et al, 2015a).…”
unclassified